Gasdermin D deficiency attenuates arthritis induced by traumatic injury but not autoantibody-assembled immune complexes - Tong Yang (BMC, 2021)
Abstract Background Gasdermin D (GSDMD) is cleaved by several proteases including by caspase-1, a component of intracellular protein complexes called inflammasomes. Caspase-1 also converts pro-interleukin-1β (pro-IL-1β) and pro-IL-18 into bioactive IL-1β and IL-18, respectively. GSDMD amino-terminal fragments form plasma membrane pores, which mediate the secretion of IL-1β and IL-18 and cause the inflammatory form of cell death pyroptosis. Here, we tested the hypothesis that GSDMD contributes to joint degeneration in the K/BxN serum transfer-induced arthritis (STIA) model in which autoantibodies against glucose-6-phosphate isomerase promote the formation of pathogenic immune complexes on the surface of myeloid cells, which highly express the inflammasomes. The unexpected outcomes with the STIA model prompted us to determine the role of GSDMD in the post-traumatic osteoarthritis (PTOA) model caused by meniscus ligamentous injury (MLI) based on the hypothesis that this pore-forming protein is activated by signals released from damaged joint tissues. Methods Gsdmd +/+ and Gsdmd −/− mice were injected with K/BxN mouse serum or subjected to MLI to cause STIA or PTOA, respectively. Paw and ankle swelling and DXA scanning were used to assess the outcomes in the STIA model whereas histopathology and micro-computed tomography (μCT) were utilized to monitor joints in the PTOA model. Murine and human joint tissues were also examined for GSDMD, IL-1β, and IL-18 expression by qPCR, immunohistochemistry, or immunoblotting. Results GSDMD levels were higher in serum-inoculated paws compared to PBS-injected paws. Unexpectedly, ablation of GSDMD failed to reduce joint swelling and osteolysis, suggesting that GSDMD was dispensable for the pathogenesis of STIA. GSDMD levels were also higher in MLI compared to sham-operated joints. Importantly, ablation of GSDMD attenuated MLI-associated cartilage degradation (p = 0.0097), synovitis (p = 0.014), subchondral bone sclerosis (p = 0.0006), and subchondral bone plate thickness (p = 0.0174) based on histopathological and μCT analyses. Conclusion GSDMD plays a key role in the pathogenesis of PTOA, but not STIA, suggesting that its actions in experimental arthropathy are tissue context-specific.